GRAND-stream: A galois-ring-based lightweight stream cipher for battery-limited internet of things (IoT) devices - Nahom Gebeyehu Zinabu; Yihenew Wondie Marye; Kula Kekeba Tune; Samuel Asferaw Demilew (Indonesian Journal of Electrical Engineering and Computer Science, 2026)
GRAND-Stream is a new lightweight stream encryption framework based on arithmetic over Galois rings that targets battery-constrained internet of things (IoT) devices. Unlike traditional LFSR/NLFSR-based designs, GRAND-stream uses ring-squaring-induced nonlinearity and inter component polynomial coupling to improve algebraic complexity while keeping compact implementation qualities. We give an explicit parameterized construction for Z2 n[x]/(f(x)), specify its state updating and output functions, and investigate algebraic degree growth and diffusion behavior. The security arguments are heuristic, based on explicitly stated assumptions about the difficulty of solving quadratic systems over Galois rings. Energy per bit, cycle count, and gate complexity are estimated using an analytical performance model. Although initial findings show potential compactness, more research is needed for thorough cryptanalysis and empirical validation on embedded devices. Therefore, GRAND-stream should be considered a structured algebraic design concept that needs more assessment.